Humoral Responses Elicited by Adenovirus Displaying Epitopes Are Induced Independently of the Infection Process and Shaped by the Toll-Like Receptor/MyD88 Pathway - Anchim, Aleksandra; Raddi, Najat; Zig, Lena; Perrieau, Patrick; Le Goffic, Ronan; Ryffel, Bernhard; Benihoud, Karim (Frontiers in Immunology, 2018)
The use of serotype 5 adenovirus (Ad)-derived vectors in vaccination is confronted to pre-existing anti-Ad immunity. Epitope display on Ad capsid is currently being investigated as an alternative approach of vaccination. The present study seeks to better understand virus- and host related factors controlling the efficacy of this new vaccination approach. In contrast to an Ad vector expressing ovalbumin as a transgene, Ad displaying an ovalbumin-derived B-cell epitope inserted into the fiber protein was able to elicit antibody responses in both Ad-naive and Ad-immune mice. Moreover, introduction of a set of mutations abrogating Ad interaction with their receptors did not modify the virus capacity to elicit a humoral response against the inserted epitope while reducing their capacity to mount antibody responses against the transgene product. Taken as a whole these data indicate that the efficacy of Ad displaying epitopes requires neither Ad binding to its receptors nor the infection process. In addition, the use of genetically deficient mice demonstrated that both TLR/MyD88 and RIG-I/MAVS innate immunity pathways were dispensable to mount anti-epitope antibody responses. However, they also revealed that TLR/MyD88 pathway but not RIG-I/MAVS pathway controls the nature of antibodies directed against the displayed epitope.